Urban malaria: primary caregivers’ knowledge, attitudes, practices and predictors of malaria incidence in a cohort of Ugandan children - Njama, Denise; Dorsey, Grant; Guwatudde, David; Kigonya, Kate; Greenhouse, Bryan; Musisi, Stephen; Kamya, Moses R. (Tropical medicine & international health, 2003)
To assess malaria-related knowledge, attitude and practices (KAP) among primary caregivers, to identify associations between primary caregivers characteristics and positive KAP towards malaria, and to identify independent predictors of childhood malaria incidence in an urban setting. methods Children aged 6 months to 5 years living in Kampala, Uganda were enrolled as part of a longitudinal study on antimalarial therapy. Primary caregivers of 307 children were interviewed and information was collected on demographics, malaria-related KAP, environmental and household factors. Malaria incidence was measured prospectively using passive surveillance. results A total of 90% of respondents reported mosquitoes and/or malaria as the cause of fever. Caregivers reported that if their child had fever, 63% would go to a clinic or hospital as their first action and 97% as their first or second action. Only 38% knew that chloroquine was the recommended firstline treatment for malaria and 29% knew the correct dose. Preventive measures for malaria were reported in 45% of households but only 25% reported using bednets. Higher levels of education for the caregiver were associated with positive malaria-related KAP. Malaria incidence varied widely. The following were independent predictors of malaria incidence: (1) Children aged 24–41 months at enrolment had a higher incidence of malaria. (2) Reported bednet or chemoprophylaxis use reduced the incidence of malaria. (3) A child’s place of residence was associated with incidence. (4) Children from households using open water sources had a higher incidence than those using closed sources. conclusion Primary caregivers were knowledgeable about malaria and used modern health care facilities but knew less about the proper administration of antimalarials and had limited use of preventive measures. Malaria incidence was associated with child’s age at enrolment, geography, source of water and the use of preventive measures.
Keywords: Malaria; Urban; Incidence; Cohort; KAP; Predictors